Delayed diagnosis of an upper cervical epidural abscess masked due to crowned dens syndrome. Issue 5 (20th May 2020) - Sugimoto, Hiroshi; Hayashi, Takuji; Nakadomari, Shun; Sugimoto, Keisuke
Abstract : An 87-year-old Japanese man presented to our hospital with a 5-day history of fever and neck pain. On physical examination, his stiff neck indicated restricted movement, especially on rotation. CT of the head revealed calcification of the atlantoaxial joint consistent with crowned dens syndrome, and celecoxib was started. Four days later, he returned to our emergency department as his neck pain and fever had not improved. Pneumonia and a urinary tract infection were suspected. The day following admission, blood culture results were positive for methicillin-resistant Staphylococcus aureus . A contrast-enhanced CT revealed an upper cervical epidural abscess at the level of C1–C2. He was discharged following 8 weeks of antibiotic treatment.